The injustices of rapid tourism growth: From recognition to restoration. (November 2022) - Rastegar, Raymond; Ruhanen, Lisa
Abstract: There is growing appreciation globally of the role tourism can play in promoting justice and equity. Nevertheless, local communities, particularly in developing countries, continue to experience injustices related to tourism development. Drawing upon the concept of justice in tourism, this paper empirically examines the four justice dimensions of distribution, procedure, recognition and restoration in the case of tourism development in the heritage city of Yazd, Iran. This study illustrates how a failure to address injustice in a rapid tourism development can negatively affect the local community's perceptions, well-being, and livelihoods. This study suggests that addressing justice in tourism will require a deliberate process that allows for the recognition of different worldviews based on integrating local values and equal dignity. Highlights: Resident perceptions of justice and fairness are frequently neglected in tourism. Residents express concerns with exclusion from decision-making. Failure to address social concerns jeopardise sustainable tourism objectives. Sustainable tourism must include what justice as recognition represents.